Efektivitas Straegi Bauran Promosi Oleh_Oleh Makanan Khas Riau (Studi Kasus Pada Wisatawan Di Kota Pekanbaru) - lubis, nurhayani; KHAIRANI, ZULIA (Komunitas Manajemen Kompetitif, 2017)
For the sake of promoting and inviting tourist to tourist resort, there are some factors that should be considered as value added. One of them is spesific foods as part of local culture characteristic. Promotional activities is an important role to introduce and cultivate the interest of tourists in a souvenir typical regional foods. The aims of the study were to analyze the level of promotion mix consists of advertising, sales promotion, direct marketing, personal selling, and public relations, and to find out the level of consumer buying interest, and finally investigate the influence of promotional mix on consumer purchase intention of the tourists. The sample in this study were 100 tourists. The method used were combination of quantitative and qualitative analysis. The data was purposively taken using quantitative analysis. Quantitative analysis, that is, descriptive analysis was performed with the interpretation of the data obtained in the study and the results of data processing that had been carried out by providing information and explanations. The results showed that advertising, personal selling, and public relations are in good criteria. While sales promotion and direct marketing are in medium criteria. Keywords: advertising, sales promotion, direct marketing, personal selling, and public relations, promotions mix